Ultraviolet irradiation promotes FOXP3 transcription via p53 in psoriasis. Issue 7 (26th February 2016) - Zhang, Dongmei; Chen, Yang; Chen, Ling; Yang, Riyao; Wang, Li; Liu, Wenying; Zhai, Zhifang; Shen, Zhu
Abstract: The decrease of forkhead box P3‐positive (FOXP3 + ) regulatory T cells (Tregs) causes an immune imbalance with effector T cells in psoriasis. Previous studies have demonstrated that in addition to its known effects on keratinocytes and effector T cells, ultraviolet (UV) irradiation alleviates psoriasis via the upregulation of FOXP3 + Tregs. However, the mechanism is unclear. Here, we found that FOXP3 + T cells were increased in psoriatic lesions after UVB irradiation ( t ' = 3.7006, P < 0.01), as determined by immunohistochemical staining. In addition, the levels of FOXP3 and p53, one of the downstream targets of UV irradiation, showed accordant changes after UV irradiation. Experiments that used a MAPK inhibitor, p53 mutant cell lines, p53 inhibitor and p53 shRNA showed a decrease in FOXP3 levels, suggesting that p53 is required for UV‐induced FOXP3 transcription. Next, we demonstrated that there are two binding sites for p53 on FOXP3 by informatics tools, a dual‐luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay. One binding site (−1771 to −1583) is located at the promoter region and is adjacent to a previously reported p53‐binding region in breast cancer cells. The other (+3845 to +4042) is located within the first intron and has not been previously reported. Our study demonstrated that FOXP3 is regulated, at least in part, by the binding of p53 to several binding sites in the promoter and intron regions following UV irradiation in psoriasis. It will be helpful to further clarify the regulatory mechanism of FOXP3 transcription and to provide new insights into the mechanisms that mediate the effects of UV irradiation in autoimmune skin disorders.